Rare bird documentation form for Peregrine Falcon at Waterloo Greenbelt, 1984 - Myers, Robert K.et al (1984)
Rare bird documentation form for a Peregrine Falcon at Waterloo Greenbelt at Black Hawk County, IA on September 10, 1984. Epson - sheet feed